Polymer, composite electrolyte, negative electrode sheet, and solid-state battery
Patent Information
- Application Number
- CN202611167123.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-27
AI Technical Summary
[0003]在复合的制备工艺中通常需引入粘结剂来实现复合,然而常用到的粘结剂往往更注重其机械粘附作用,自身离子传导能力有限,使得极片内部传输阻抗增大,同时粘结剂与硫化物固态电解质的相容性不足,可能会造成界面稳定性下降,进而使得极片在循环过程中出现阻抗持续上升、首次库伦效率下降以及倍率性能下降等问题
[0030]本发明中的聚合物包括嵌段A与嵌段B,嵌段A与嵌段B相互键合串联构成连续的聚合物碳-碳主链,聚合物侧链即为嵌段A与嵌段B各自携带的支链,由上述式1和式2可知,嵌段A对应的聚合物侧链为聚二氧戊烷侧链,嵌段B对应的聚合物侧链为酯基侧链。聚合物中的聚二氧戊烷侧链以及酯基侧链中的酯基和R基团相互协同,使得聚合物作为粘结剂能够在匹配硫化物固态电解质的溶剂体系下,有效改善粘结剂在弱极性溶剂中的相容性以及粘结剂与硫化物固态电解质的界面兼容性并提高负极内部的离子传导效率、以及负极内各组分间的界面粘接力,进而使得固态电池具有较高的首次库伦效率和倍率性能。
Smart Images

Figure SMS_5 
Figure QLYQS_1 
Figure QLYQS_2
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, and particularly relates to a polymer, a composite electrolyte, a negative electrode, and a solid-state battery. Background Technology
[0002] Solid-state and semi-solid-state batteries, with their significant advantages such as high safety and high energy density, have shown broad application prospects in fields such as electric vehicles and large-scale energy storage systems. Among various solid electrolyte systems, sulfide solid electrolytes have become an important research direction due to their excellent ionic conductivity and good mechanical ductility. To achieve high energy density in sulfide-based solid-state batteries, silicon-containing materials with a capacity of approximately 4200 mAh / g are typically required. However, silicon-containing materials have inherently low electronic and ionic conductivity, and the lack of wetting effect from liquid electrolytes in solid-state batteries severely limits their rate performance. Currently, combining silicon-containing materials with sulfide solid electrolytes is one of the effective ways to improve performance, but this also places higher demands on the composite preparation process.
[0003] In the composite preparation process, a binder is usually required to achieve the composite. However, commonly used binders often focus more on their mechanical adhesion and have limited ion conduction capacity, which increases the internal transmission impedance of the electrode. At the same time, the compatibility between the binder and the sulfide solid electrolyte is insufficient, which may cause a decrease in interface stability. As a result, the electrode will experience problems such as a continuous increase in impedance, a decrease in initial coulombic efficiency, and a decrease in rate performance during cycling.
[0004] Therefore, how to simultaneously consider ion transport efficiency, interface stability, and electrode structure integrity in a silicon-containing material and sulfide solid electrolyte composite system in order to improve the first coulombic efficiency and rate performance of solid-state batteries has become a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] One objective of this invention is to provide a polymer that simultaneously considers ion transport efficiency, interface stability, and electrode structure integrity, thereby improving the initial coulombic efficiency and rate performance of solid-state batteries; a second objective is to provide a composite electrolyte; a third objective is to provide a negative electrode; and a fourth objective is to provide a solid-state battery.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] A first aspect of the present invention provides a polymer comprising block A and block B, wherein block A is a structural unit shown in Formula 1 and block B is a structural unit shown in Formula 2.
[0008] Formula 1, Formula 2;
[0009] In Equation 1, x is an integer from 4 to 15; in Equation 2, R is selected from any one of the bases -CF3, -CH2CF3, -C(CF3)3, and -Ph.
[0010] The number of repeating units in block A is m, 1≤m≤5, and the number of repeating units in block B is n, 20≤n≤160, where m and n are integers.
[0011] Based on the above technical means, polymers, as binders, can effectively improve the compatibility of binders in weakly polar solvents and the interfacial compatibility between binders and sulfide solid electrolytes in solvent systems that match sulfide solid electrolytes. They can also improve the ion conduction efficiency inside the negative electrode and the interfacial adhesion between the components inside the negative electrode, thereby enabling solid-state batteries to have higher initial coulombic efficiency and rate performance.
[0012] Furthermore, the number-average molecular weight of the polymer is Mn, with 3000 g / mol ≤ Mn ≤ 50000 g / mol.
[0013] Based on the above technical means, it is beneficial to form a continuous bonding and conduction network, and at the same time, it can better buffer the volume change of silicon-containing materials during charge and discharge cycles, thereby further improving the first coulombic efficiency and rate performance of solid-state batteries.
[0014] A second aspect of the present invention provides a composite electrolyte comprising a lithium salt and a polymer of the first aspect.
[0015] Furthermore, the lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(oxalateborate), lithium difluorooxalateborate, lithium perchlorate, and lithium bis(trifluoromethanesulfonyl)imide; the mass ratio of lithium salt to polymer is (10~40):(60~90).
[0016] Based on the aforementioned technical means, the use of the lithium salt helps ensure the structural integrity and interfacial contact stability of the electrode during charging and discharging, thereby improving the rate performance and cycle performance of the solid-state battery. Furthermore, by controlling the mass ratio of lithium salt to polymer within the aforementioned range, it is beneficial to construct a continuous and interconnected ion transport pathway, effectively improving the ion conduction efficiency within the negative electrode, reducing the internal transport impedance of the electrode, and thus improving the initial coulombic efficiency and rate performance of the solid-state battery.
[0017] A third aspect of the present invention provides a negative electrode sheet, the negative electrode sheet comprising a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector, the negative electrode active layer comprising a composite electrolyte of the second aspect.
[0018] Furthermore, based on the mass of the negative electrode active layer, the total mass percentage of polymer and lithium salt is 2.0% to 8.0%.
[0019] Based on the above technical means, it is beneficial to improve the ion conduction capacity in the negative electrode and enhance the interfacial adhesion between the components in the negative electrode, while also helping to reduce the loss of energy density in solid-state batteries.
[0020] Furthermore, the negative electrode active layer also includes a solid electrolyte, which includes Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 Li 10 GeP2S 12 At least one of the following; and / or, the negative electrode active layer further includes an adhesive, the adhesive including at least one of polyisobutylene, styrene-ethylene-butene-styrene block copolymer, hydrogenated nitrile rubber, nitrile rubber, and styrene-butadiene rubber.
[0021] Based on the above-mentioned technical means, it is beneficial to further improve the rate performance and initial coulombic efficiency of solid-state batteries.
[0022] A fourth aspect of the present invention provides a solid-state battery, including the negative electrode sheet of the third aspect.
[0023] Furthermore, the solid-state battery is a semi-solid mold half-cell, which also includes a solid electrolyte sheet. Along the thickness direction of the solid electrolyte sheet, the solid electrolyte sheet includes a first surface and a second surface. The first surface is wetted with an ionic liquid and is disposed facing the negative electrode sheet.
[0024] Based on the above technical means, a highly conductive liquid phase ion transport transition layer can be constructed between the solid electrolyte sheet and the negative electrode sheet, while maintaining effective contact between the negative electrode and the solid electrolyte sheet, significantly reducing the solid-solid interface impedance on the negative electrode side, improving lithium ion transport kinetics, and enabling the solid-state battery to have higher rate performance.
[0025] Furthermore, the ionic liquid includes at least one of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bisfluorosulfonylimide, 1-n-butyl-1-methylpyrrolidineonium bisfluorosulfonylimide, 1-ethyl-3-methylimidazolium bistrifluoromethylsulfonylimide, 1-methyl-3-hexylimidazolium fluoromethylsulfonylimide, N-ethyl-N-methylpyrrolidine bis(fluorosulfonic acid)imide, N-propyl-N-methylpyrrolidine bis(fluorosulfonic acid)imide, and 1-methyl-1-propyl-3-fluoropyrrole bis(fluorosulfonic acid)imide.
[0026] Based on the above technical means, ionic liquids can preferentially undergo controllable reduction during the first charge cycle, generating a dense and stable LiF-rich solid electrolyte interphase (SEI) film on the negative electrode surface. This effectively suppresses irreversible side reactions at the negative electrode interface, reduces permanent loss of active lithium, and further improves the first coulombic efficiency of solid-state batteries.
[0027] Furthermore, the mass percentage of ionic liquid in the solid electrolyte sheet is w, where 15% ≤ w ≤ 25%.
[0028] Based on the above-mentioned technical means, it is beneficial to construct an efficient lithium-ion transport channel and improve the rate performance of solid-state batteries; at the same time, it is beneficial to generate a dense and stable SEI film on the negative electrode surface, reduce irreversible active lithium consumption, and significantly improve the first coulombic efficiency of solid-state batteries.
[0029] The beneficial effects of this invention are:
[0030] The polymer in this invention comprises block A and block B, which are bonded together in series to form a continuous polymer carbon-carbon backbone. The polymer side chains are the branches carried by each of block A and block B. As shown in Formulas 1 and 2 above, the polymer side chain corresponding to block A is a polydioxopentane side chain, and the polymer side chain corresponding to block B is an ester side chain. The polydioxopentane side chain and the ester and R groups in the ester side chains of the polymer work synergistically, enabling the polymer to effectively improve the compatibility of the binder in weakly polar solvents and the interfacial compatibility between the binder and the sulfide solid electrolyte in a solvent system that matches the sulfide solid electrolyte. This also improves the ion conduction efficiency inside the negative electrode and the interfacial adhesion between the components inside the negative electrode, thereby enabling the solid-state battery to have higher initial coulombic efficiency and rate performance. Detailed Implementation
[0031] The following description, with reference to preferred embodiments, illustrates the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and various details in this specification can be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. It should be understood that the preferred embodiments are merely illustrative of the present invention and not intended to limit the scope of protection of the present invention.
[0032] In the composite manufacturing process, a binder is usually required to achieve the composite effect. The main methods are divided into dry composite and wet composite. Currently, the most commonly used binder in dry composite is polytetrafluoroethylene (PTFE). However, this binder has poor reduction stability and is not suitable for use in the negative electrode. Therefore, wet composite is generally considered for preparing the negative electrode sheet. Through research and analysis, the inventors found that although traditional polymeric binders (such as styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polyacrylic acid (PAA), etc.) can provide a certain degree of adhesion, they have the following inherent defects: (1) The binder itself is an ion insulator, which will hinder the transport of active ions inside the negative electrode and increase the internal resistance of the negative electrode; (2) The polar binder has poor interfacial compatibility with the sulfide solid electrolyte and is prone to interfacial side reactions or phase separation; (3) The sulfide solid electrolyte is sensitive to strongly polar (dielectric constant ≥30 at 25℃±5℃) solvents (such as N-methylpyrrolidone (NMP) and water) and is prone to decomposition. It needs to be dispersed in weakly polar (dielectric constant <10 at 25℃±5℃) solvents (such as isobutyl isobutyrate, diethyl succinate, ethyl acetate, butyl acetate, butyl butyrate, octyl acetate, anisole, etc.), but the above polymeric binders are difficult to dissolve or disperse in weakly polar solvents. Therefore, in wet lamination, polymeric binders such as polyisobutylene (PIB) and styrene-ethylene-butene-styrene block copolymer (SEBS) that are soluble in weakly polar solvents are generally used. However, these binders generally suffer from problems such as insufficient adhesion and obstruction of ion transport channels within the negative electrode.
[0033] Therefore, for silicon-containing materials and sulfide solid electrolyte composite systems, it is necessary to develop a binder that can improve the solvent compatibility of the binder and the interfacial compatibility between the binder and the sulfide solid electrolyte in a solvent system that matches the sulfide solid electrolyte, and improve the ion conduction efficiency inside the negative electrode and the interfacial adhesion between the components inside the negative electrode, so as to improve the first coulombic efficiency and rate performance of solid-state batteries.
[0034] Based on this, the first aspect of the present invention provides a polymer comprising block A and block B, wherein block A is a structural unit shown in Formula 1 and block B is a structural unit shown in Formula 2.
[0035] Formula 1, Formula 2;
[0036] In Equation 1, x is an integer from 4 to 15; in Equation 2, R is selected from any one of the bases -CF3, -CH2CF3, -C(CF3)3, and -Ph.
[0037] The number of repeating units in block A is m, 1≤m≤5, and the number of repeating units in block B is n, 20≤n≤160, where m and n are integers.
[0038] For example, the value of x can be 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, or a range of any two values therein; the value of m can be 1, 2, 3, 4 or 5, or a range of any two values therein; the value of n can be 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155 or 160, or a range of any two values therein.
[0039] It should be noted that the present invention does not specifically limit the arrangement of block A and block B in the polymer molecular chain. The two can be connected in any combination of blocks, and all can achieve the technical effect of the present invention. For example, they can be random blocks, diblocks (AB), triblocks (ABA, BAB), or multiple blocks arranged alternately, etc., and the above arrangement does not affect the implementation of the technical solution of the present invention.
[0040] The polymer in this invention includes block A and block B, which are bonded together in series to form a continuous polymer carbon-carbon backbone. The polymer side chain is the branch chain carried by each of block A and block B. As can be seen from the above formulas 1 and 2, the polymer side chain corresponding to block A is a polydioxopentane side chain, and the polymer side chain corresponding to block B is an ester side chain. Among them, the polydioxopentane side chain has a high degree of freedom of chain segment movement and lithium salt dissociation ability. On the one hand, the ether oxygen group in the polydioxopentane side chain can coordinate and complex with lithium ions, promote the full dissociation of lithium salt, and release more free lithium ions. At the same time, the highly flexible chain segment can undergo rapid dynamic conformational transformation, which can build a through and continuous lithium ion transport pathway in the negative electrode active layer, effectively improve the ion conduction efficiency inside the negative electrode, reduce the internal transport impedance of the electrode, and thus improve the first coulombic efficiency and rate performance of the solid-state battery. On the other hand, the flexible ether oxygen long chain contained in the polydioxopentane side chain has excellent elastic buffering characteristics. During the charge and discharge cycle of silicon-containing materials, it can dynamically adapt to the huge volume expansion and contraction deformation of silicon-containing materials through chain segment stretching and curling, absorb the internal stress generated by the volume change of silicon-containing materials, and thus effectively improve the structural stability of the electrode. The ester group in the ester side chain can form ion-dipole interactions with the sulfide solid electrolyte and hydrogen bonds with the surface groups of the negative electrode active material, achieving excellent adhesion between the components in the negative electrode active layer and improving the interfacial adhesion between the components in the negative electrode. At the same time, the R group in the ester side chain can regulate the nucleophilicity of the ester group. When the R group is selected from -CF3, -CH2CF3 or -C(CF3)3, the strong electron-withdrawing inductive effect of the F atom can be used to reduce the electron cloud density of the ester oxygen, suppress the nucleophilic attack of the lone pair of ester oxygen on the sulfide solid electrolyte, and reduce the structural damage and side reactions of the sulfide solid electrolyte. When the R group is -Ph (phenyl), the -Ph group, as a conjugated stabilizing group, can use its steric hindrance effect to disperse the negative charge on the ester oxygen, thereby reducing the side reactions between the polar group and the sulfide solid electrolyte. The polymer carbon-carbon backbone can endow the molecular skeleton with excellent mechanical strength and structural stability. During solvent evaporation and solid-state battery charge-discharge cycles, it can effectively stabilize the continuous three-dimensional bonding network built by the polymer, maintain long-term close contact between the polymer and the components in the negative electrode active layer and the negative electrode current collector, significantly improve the interfacial adhesion of the electrode, improve the structural integrity of the electrode, and at the same time ensure that the functional side chains can fully play their role at the interface.Furthermore, the polymer in this invention possesses both polydioxanone side chains and ester side chains. It can generally be dissolved using ester solvents (such as isobutyl isobutyrate, diethyl succinate, ethyl acetate, butyl acetate, butyl butyrate, octyl acetate, etc.). The ester groups in the ester side chains and the ester groups in the solvent have the same electron donor-acceptor characteristics. When the polymer is dispersed in the solvent, the C=O double bonds in the solvent molecules can effectively replace the original physical crosslinking points between polymer chains (such as interchain dipole attraction), forming new, dynamic dipole-dipole interactions with the polymer side chains. This "same kind" The "displacement" process results in a significant solvation exothermic effect, greatly reducing the activation energy required for polymer chain segment de-entanglement and driving the spontaneous extension of macromolecular chains and uniform dispersion in the solvent. When the polydioxopentane side chain accounts for a large proportion of the polymer, ether solvents (such as anisole) are more likely to dissolve it. According to the principle of "like dissolves like," both the polymer and the solvent have ether-oxygen bonds, making the dissolution process thermodynamically easier. In addition, the ether-oxygen atoms in the polydioxopentane side chain are good hydrogen bond acceptors, which can form weak hydrogen bonds with the aromatic ring of anisole, allowing the anisole molecules to effectively surround and separate the polymer chain, thereby promoting dissolution.
[0041] When the value of x is too small, for example, less than the lower limit of this invention, the length of the polydioxopentane side chain is insufficient, which leads to fewer ether-oxygen coordination sites provided by the polydioxopentane side chain, reducing the chain segment mobility of lithium ions and restricting ion migration kinetics; it also results in a lack of flexibility in the polymer, making it unable to effectively buffer the volume expansion effect of silicon-containing materials during electrochemical processes. When the value of x is too large, for example, greater than the upper limit of this invention, the length of the polydioxopentane side chain is too long, which may cause an excessively high proportion of flexible soft segments in the polymer system, resulting in a decrease in the overall mechanical strength and structural stability of the polymer, affecting the structural stability of the electrode; at the same time, excessively long polydioxopentane side chains are prone to disordered winding and local entanglement, restricting the dynamic movement ability of chain segments, blocking lithium ion transport pathways, and causing an increase in the ion conduction impedance of the electrode.
[0042] When the value of m is too small, for example, less than the lower limit of the present invention, m=0, the polymer contains only block B, and lacks the excellent lithium salt dissociation function, lithium conduction function and buffering function of the polydioxopentane chain segment as well as the function of buffering the volume expansion effect of silicon-containing materials; when the value of m is too large, for example, greater than the upper limit of the present invention, the number average molecular weight of block A in the polymer is too high, which reduces the solubility of the polymer in weakly polar ester solvents.
[0043] When the value of n is too small, for example, less than the lower limit of the present invention, there are too few ester side chains in the polymer, which is not conducive to improving the interfacial adhesion between the components in the negative electrode; when the value of n is too large, for example, greater than the upper limit of the present invention, there are too many ester side chains in the polymer, which will to some extent aggravate the side reaction between the polymer and the sulfide electrolyte, affecting the first coulombic efficiency of the solid-state battery.
[0044] Therefore, the polymer in this invention, as a binder, can effectively improve the compatibility of the binder in weakly polar solvents and the interfacial compatibility between the binder and the sulfide solid electrolyte in a solvent system that matches the sulfide solid electrolyte. It can also improve the ion conduction efficiency inside the negative electrode and the interfacial adhesion between the components inside the negative electrode, thereby enabling the solid-state battery to have higher initial coulombic efficiency and rate performance.
[0045] In one specific embodiment, the number-average molecular weight of the polymer is Mn, with a value between 3000 g / mol and 50000 g / mol. By controlling the value of Mn within this range, the number-average molecular weight of the polymer is moderate, which is beneficial for its uniform dispersion among the components such as the negative electrode active material, sulfide solid electrolyte, and conductive agent during slurry preparation and coating, forming a continuous bonding and conductive network. At the same time, it can better buffer the volume changes of silicon-containing materials during charge-discharge cycles, reduce the risk of contact relaxation and / or bonding failure between solid particles, thereby effectively improving the structural integrity of the electrode and making the lithium-ion transport path within the electrode more continuous, further improving the initial coulombic efficiency and rate performance of the solid-state battery.
[0046] For example, the value of Mn can be 3000 g / mol, 5000 g / mol, 10000 g / mol, 15000 g / mol, 20000 g / mol, 25000 g / mol, 30000 g / mol, 35000 g / mol, 40000 g / mol, 45000 g / mol or 50000 g / mol, or a range of any two of these values.
[0047] In this invention, the number-average molecular weight (Mn) of the polymer can be controlled by adjusting the molar ratio of monomers (including the first and second monomers) to chain transfer agents, the percentage of initiator molars in the total monomer molar ratio, the total molar concentration of monomers, or the molar ratio of the first monomer to the second monomer during the polymer preparation process. For example, under constant conditions, increasing the molar ratio of monomers to chain transfer agents (i.e., increasing the monomer content per unit of chain transfer agent) increases the theoretical degree of polymerization and increases Mn, and vice versa; or, under constant conditions, increasing the molar ratio of initiator to monomers decreases Mn, and vice versa; or, under constant conditions, increasing the total molar concentration of monomers increases Mn, and vice versa; or, under constant conditions and with a constant target total degree of polymerization, increasing the molar ratio of the first monomer to the second monomer increases Mn, and vice versa.
[0048] In this invention, the number-average molecular weight (Mn) of the polymer can be obtained by the following method:
[0049] 1) Dry the polymer to obtain the sample to be tested; weigh 5 mg to 10 mg of the sample to be tested and mix it with chromatographic grade tetrahydrofuran (THF), and shake or sonicate at room temperature until the sample to be tested is completely dissolved to prepare a test solution of 2 mg / mL to 5 mg / mL.
[0050] 2) Use a polytetrafluoroethylene (PTFE) organic filter membrane to filter the above test solution to remove impurities such as particles, gels and dust; if the test sample contains salt or inorganic residues, the test solution should first be passed through precipitation, dialysis or short column to remove the salt or inorganic residues.
[0051] 3) The mobile phase is THF, the flow rate is 1.0 mL / min, the column temperature is 35℃, the detector is an RI detector, which can be used with a UV or MALS detector. The injection volume is 50μL~100μL. A calibration curve is established using a narrow-distribution PMMA standard. The number-average molecular weight (Mn) of the polymer is obtained by integration using GPC software.
[0052] In one embodiment, the polymer is prepared by a preparation method comprising the following steps:
[0053] (1) Prepare the structure CH2=CH-(CH2CH2OCH2O) x The first monomer of -CH3 and the second monomer of the structural formula CH2=CH-C(=O)-OR, wherein x is an integer from 4 to 15, and R is selected from any one of -CF3, -CH2CF3, -C(CF3)3, and -Ph group;
[0054] (2) The mixed solution including the first monomer, the second monomer, the chain transfer agent, the initiator and the solvent is subjected to deoxygenation treatment, and the mixed solution is subjected to polymerization reaction at 60°C~70°C. After the reaction is completed, the reaction system is subjected to precipitation treatment and purification treatment in sequence to obtain the polymer of the present invention.
[0055] The present invention does not specifically limit the preparation method of the first monomer in step (1), as long as it can achieve the purpose of the present invention.
[0056] In one embodiment, the first monomer is prepared by a preparation method including the following steps:
[0057] 1) Under a protective atmosphere, a cationic ring-opening polymerization catalyst was added to a mixed solution containing 1,3-dioxolane, 3-buten-1-ol, and a first solvent at a temperature of 0℃~5℃. After maintaining the temperature, the first reaction was carried out at 20℃~25℃. After the reaction was completed, the reaction system was subjected to a first quenching treatment and a first purification treatment in sequence to obtain the structure CH2=CH-(CH2CH2OCH2O). x-H intermediate;
[0058] 2) Under a protective atmosphere, sodium hydride and iodomethane were added sequentially to a mixed solution containing the above intermediate and the second solvent at a temperature of 0℃~5℃. After maintaining the temperature, a second reaction was carried out at a temperature of 20℃~25℃. After the reaction was completed, the reaction system was subjected to a second quenching treatment and a second purification treatment to obtain the structure CH2=CH-(CH2CH2OCH2O). x The first monomer of -CH3.
[0059] Specifically, in step 1), under a protective atmosphere, 1,3-dioxolane (CAS: 646-06-0) is added to a mixture of 3-buten-1-ol (CAS: 627-27-0) and the first solvent at a temperature of 0℃~5℃ to obtain a mixed solution. A cationic ring-opening polymerization catalyst is then added to the mixed solution, and the temperature is maintained at 0℃~5℃. After the maintenance, the temperature is raised to 20℃~25℃ to carry out the first reaction. After the reaction, the reaction system is subjected to a first quenching treatment and a first purification treatment in sequence to obtain the structure CH2=CH-(CH2CH2OCH2O). x -H is an intermediate form where x is an integer from 4 to 15.
[0060] The reaction equation in step 1) is: CH2=CH-CH2-CH2-OH + x 1,3-dioxolane → CH2=CH-(CH2CH2OCH2O) x -H.
[0061] For example, in step 1), the temperature of the mixing system can be 0°C, 1°C, 2°C, 3°C, 4°C or 5°C, or a range of any two of these values; the temperature of the heat preservation can be 0°C, 1°C, 2°C, 3°C, 4°C or 5°C, or a range of any two of these values; the temperature of the first reaction can be 20°C, 21°C, 22°C, 23°C, 24°C or 25°C, or a range of any two of these values.
[0062] This invention does not specifically limit the types of the above-mentioned cationic ring-opening polymerization catalyst and the first solvent, as long as they can achieve the purpose of this invention. For example, the cationic ring-opening polymerization catalyst can be trifluoromethanesulfonic acid (TfOH, CAS: 1493-13-6, molecular formula: CF3SO3H) and / or boron trifluoride diethyl ether complex (BF3·Et2O, CAS: 109-63-7, molecular formula C4H). 10 (BF3O), the first solvent can be anhydrous toluene.
[0063] The present invention does not impose a specific limit on the heat preservation time in step 1), but can adjust it according to the actual situation, as long as the purpose of the present invention can be achieved. For example, the heat preservation time can be 1h to 2h.
[0064] The present invention does not impose a specific limit on the time of the first reaction in step 1), but can adjust it according to the actual situation, as long as the purpose of the present invention can be achieved. For example, the time of the first reaction can be 4h to 12h.
[0065] The present invention does not impose a specific limit on the heating rate in step 1), but can adjust it according to the actual situation, as long as the purpose of the present invention can be achieved.
[0066] The present invention does not specifically limit the molar ratio of 1,3-dioxolane and 3-buten-1-ol in the mixed solution. The value of x in the structural formula of the first monomer prepared can be within the above range by controlling the molar ratio of 1,3-dioxolane and 3-buten-1-ol, that is, the value of x in polymer block A is within the above range.
[0067] This invention does not impose a specific limit on the total concentration of 1,3-dioxolane and 3-buten-1-ol in the mixed solution, and can be adjusted according to the actual situation, as long as the purpose of this invention can be achieved.
[0068] The present invention does not impose a specific limit on the amount of cationic ring-opening polymerization catalyst added, which can be adjusted according to the actual situation, as long as the purpose of the present invention can be achieved.
[0069] The present invention does not specifically limit the method of the first quenching treatment, as long as it can achieve the purpose of the present invention. For example, after the first reaction is completed, triethylamine or saturated NaHCO3 aqueous solution is added to the reaction system to carry out the first quenching treatment.
[0070] The present invention does not specifically limit the method of the first purification treatment, as long as it can achieve the purpose of the present invention. For example, after the first quenching treatment, the reaction system is separated into liquid and liquid phases, the organic phase is collected, the organic phase is washed with water and brine, anhydrous magnesium sulfate is added to the washed organic phase for drying, magnesium sulfate is removed by filtration, and the filtrate is subjected to low-temperature (30℃~40℃) rotary evaporation to remove solvent and unreacted small molecule impurities to obtain the above intermediate.
[0071] In step 2), under a protective atmosphere, sodium hydride (NaH, CAS: 7646-69-7) is added to a mixed solution of the intermediate and the second solvent at a temperature of 0℃~5℃ to react and generate an alkoxide. After the reaction is complete, methyl iodide (CH3I, CAS: 74-88-4) is added to the reaction system for methylation end-capping. The system is then kept at 0℃~5℃. After the holding time, the temperature is raised to 20℃~25℃ for the second reaction. After the reaction is complete, the reaction system undergoes a second quenching treatment and a second purification treatment to obtain the structure CH2=CH-(CH2CH2OCH2O). x The first monomer of -CH3.
[0072] The reaction equation in step 2) is: CH2=CH-(CH2CH2OCH2O) x -H+NaH→CH2=CH-(CH2CH2OCH2O) x -Na+H2,CH2=CH-(CH2CH2OCH2O) x -Na+CH3I→CH2=CH-(CH2CH2OCH2O) x -CH3+NaI.
[0073] For example, in step 2), the temperature of the mixed solution can be 0°C, 1°C, 2°C, 3°C, 4°C or 5°C, or a range of any two of these values; the temperature for heat preservation can be 0°C, 1°C, 2°C, 3°C, 4°C or 5°C, or a range of any two of these values; the temperature for the second reaction can be 20°C, 21°C, 22°C, 23°C, 24°C or 25°C, or a range of any two of these values.
[0074] The present invention does not impose a specific time limit on the reaction to form alkoxide in step 2), but can adjust it according to the actual situation, as long as the purpose of the present invention can be achieved. For example, the reaction to form alkoxide can be 10 min to 60 min.
[0075] The present invention does not impose a specific limit on the heat preservation time in step 2), but can adjust it according to the actual situation, as long as the purpose of the present invention can be achieved. For example, the heat preservation time can be 30 min to 60 min.
[0076] The present invention does not impose a specific time limit on the second reaction in step 2), but can adjust it according to the actual situation, as long as the purpose of the present invention can be achieved. For example, the time of the second reaction can be 6h to 12h.
[0077] The present invention does not impose a specific limit on the heating rate in step 2), but can adjust it according to the actual situation, as long as the purpose of the present invention can be achieved.
[0078] This invention does not impose a specific limit on the molar ratio of the intermediate and NaH, which can be adjusted according to the actual situation, as long as the purpose of this invention can be achieved.
[0079] This invention does not impose a specific limit on the molar ratio of the intermediate and iodomethane, but can adjust it according to the actual situation, as long as the purpose of this invention can be achieved.
[0080] The present invention does not specifically limit the type of the second solvent, as long as it can achieve the purpose of the present invention, for example, anhydrous tetrahydrofuran can be used.
[0081] The present invention does not specifically limit the method of the second quenching treatment, as long as it can achieve the purpose of the present invention. For example, after the second reaction is completed, methanol is added to the reaction system to carry out the second quenching treatment.
[0082] This invention does not specifically limit the method of the second purification treatment, as long as it can achieve the purpose of this invention. For example, after the second quenching treatment, water is added for dilution, and extraction is performed with DCM or ethyl acetate to obtain the structure CH2=CH-(CH2CH2OCH2O). x The first monomer of -CH3.
[0083] The present invention does not specifically limit the type of protective atmosphere in steps 1) and 2) above, as long as it can achieve the purpose of the present invention. For example, nitrogen can be used as a protective atmosphere.
[0084] The present invention does not specifically limit the preparation method of the second monomer in step (1), as long as it can achieve the purpose of the present invention.
[0085] In one embodiment, the second monomer with the structural formula CH2=CH-C(=O)-OC(CF3)3 is prepared by a preparation method including the following steps:
[0086] Under a protective atmosphere, a mixed solution comprising tris(trifluoromethyl)methanol, a polymerization inhibitor, anhydrous triethylamine, and anhydrous dichloromethane was prepared at a temperature of -15℃ to -10℃. Freshly distilled acryloyl chloride was slowly and uniformly added dropwise to the mixed solution with stirring, while controlling the temperature of the mixed solution to be ≤-5℃ during the addition. After the addition was completed, the reaction was carried out at -15℃ to -10℃. After the reaction was completed, the reaction system was subjected to a third quenching treatment and a third purification treatment in sequence to obtain a second monomer with the structural formula CH2=CH-C(=O)-OC(CF3)3.
[0087] Specifically, under a protective atmosphere, a mixed solution comprising tris(trifluoromethyl)methanol, a polymerization inhibitor, anhydrous triethylamine, and anhydrous dichloromethane was prepared. The temperature of the mixed solution was lowered to -15℃ to -10℃, and stirring was started. Freshly distilled acryloyl chloride was slowly and uniformly added dropwise to the mixed solution while stirring, and the temperature of the mixed solution was controlled to be ≤-5℃ during the addition. After the addition was completed, the reaction was carried out at -15℃ to -10℃. After the reaction was completed, the reaction system was subjected to a third quenching treatment and a third purification treatment in sequence to obtain a second monomer with the structural formula CH2=CH-C(=O)-OC(CF3)3.
[0088] For example, the temperature of the mixed solution can be -10°C, -11°C, -12°C, -13°C, -14°C or -15°C, or a range of any two of these values; the reaction temperature can be -10°C, -11°C, -12°C, -13°C, -14°C or -15°C, or a range of any two of these values.
[0089] This invention does not specifically limit the type of polymerization inhibitor, as long as it can achieve the purpose of this invention. For example, the polymerization inhibitor can be 4-methoxyphenol (MEHQ).
[0090] This invention does not impose specific limitations on the concentrations of tris(trifluoromethyl)methanol, polymerization inhibitor, and anhydrous triethylamine in the mixed solution; these concentrations can be adjusted according to actual conditions, as long as the objective of this invention can be achieved.
[0091] The present invention does not impose a specific limit on the amount of freshly distilled acryloyl chloride added, and it can be adjusted according to the actual situation, as long as the purpose of the present invention can be achieved.
[0092] The present invention does not impose a specific limit on the cooling rate during the preparation of the second monomer, but can adjust it according to the actual situation, as long as the purpose of the present invention can be achieved.
[0093] The present invention does not specifically limit the stirring method in the preparation of the second monomer. Conventional methods in the art can be used for stirring, as long as the purpose of the present invention can be achieved. For example, magnetic stirring, mechanical stirring, etc. can be used for stirring.
[0094] The present invention does not impose a specific limit on the stirring speed during the preparation of the second monomer, but can adjust it according to the actual situation, as long as the purpose of the present invention can be achieved.
[0095] The present invention does not impose a specific limitation on the dripping time of the freshly distilled acryloyl chloride, which can be adjusted according to the actual situation, as long as the purpose of the present invention can be achieved. For example, the dripping time of the freshly distilled acryloyl chloride is 1h to 3h.
[0096] The present invention does not impose a specific limit on the reaction time in the preparation of the second monomer, and it can be adjusted according to the actual situation, as long as the purpose of the present invention can be achieved. For example, the reaction time can be 10h to 16h.
[0097] The present invention does not specifically limit the source of the above-mentioned tris(trifluoromethyl)methanol, polymerization inhibitor, anhydrous triethylamine, anhydrous dichloromethane and freshly distilled acryloyl chloride, and products prepared by commercially available products or conventional preparation methods known to those skilled in the art are acceptable.
[0098] The present invention does not specifically limit the method of the third quenching treatment, as long as it can achieve the purpose of the present invention. For example, the reaction system is kept at 0℃~5℃, saturated brine at 0℃~5℃ is added, and the mixture is stirred continuously for 10min~60min.
[0099] This invention does not specifically limit the method of the third purification treatment, as long as it can achieve the purpose of this invention. For example, the quenched system is transferred to a separatory funnel, allowed to stand and separate into layers, with a lower organic phase (dichloromethane layer, containing the second monomer) and an upper aqueous phase, to obtain the organic phase; the separated organic phase is mixed with saturated saline solution at 0℃~5℃ and washed to remove triethylamine and water-soluble impurities, repeated at least twice to obtain the washed organic phase; a solid desiccant (such as anhydrous sodium sulfate) is added to the washed organic phase and dried for 3h~6h, then filtered to remove the solid desiccant, to obtain the filtrate; the filtrate is then... The liquid is removed by rotary evaporation (water bath ≤30℃ to prevent monomer thermal polymerization) to obtain crude monomer product. The crude monomer product is then loaded into a vacuum distillation apparatus. A small amount of basic alumina is added to the distillation flask beforehand to adsorb acidic impurities and inhibit polymerization. The vacuum degree is set to 10 mmHg, and the temperature is slowly increased (heating rate is 1℃ / min~3℃ / min). The main fraction is collected: the colorless and transparent fraction with a pot temperature of 72℃ / 10mmHg~75℃ / 10mmHg is CH2=CH-C(=O)-OC(CF3)3 monomer. After the fraction is cooled, it is sealed with argon and stored in a cool, dark place at 0℃~5℃.
[0100] The present invention does not specifically limit the type of protective atmosphere in the preparation process of the second monomer, as long as it can achieve the purpose of the present invention. For example, nitrogen can be used as a protective atmosphere.
[0101] Specifically, in step (2), a mixed solution comprising the first monomer, the second monomer, the chain transfer agent, the initiator and the solvent is prepared, the mixed solution is subjected to deoxygenation treatment, and the mixed solution is subjected to polymerization reaction at a temperature of 60°C to 70°C. After the reaction is completed, the reaction system is subjected to precipitation treatment and purification treatment in sequence to obtain the polymer of the present invention.
[0102] For example, the temperature of the polymerization reaction can be 60°C, 62°C, 64°C, 66°C, 68°C or 70°C, or a range of any two of these values.
[0103] Further, in step (2), the total concentration of the first monomer and the second monomer in the mixed solution is 0.3 mol / L to 0.8 mol / L. For example, the total concentration can be 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L or 0.8 mol / L, or a range of any two of these values.
[0104] The present invention does not specifically limit the molar ratio of the first monomer and the second monomer in the above mixed solution. The number of repeating units m and n of block A and block B in the prepared polymer can be kept within the above range by controlling the molar ratio of the first monomer and the second monomer.
[0105] The present invention does not impose a specific limitation on the molar ratio of initiator to monomer (including the first monomer and the second monomer) in the above mixed solution, and can be adjusted according to the actual situation, as long as the purpose of the present invention can be achieved.
[0106] The present invention does not impose a specific limitation on the molar ratio of monomers (including the first monomer and the second monomer) to chain transfer agents in the above-mentioned mixed solution, and can be adjusted according to the actual situation, as long as the purpose of the present invention can be achieved.
[0107] The present invention does not specifically limit the time of polymerization reaction in step (2), but can adjust it according to the actual situation, as long as the purpose of the present invention can be achieved. For example, the time of polymerization reaction can be 6h to 18h.
[0108] The present invention does not specifically limit the types of chain transfer agent, initiator and solvent in step (2), as long as they can achieve the purpose of the present invention. For example, the chain transfer agent can be 2-(dodecyltrithiocarbonate)-2-methylpropionic acid (DDMAT), the initiator can be azobisisobutyronitrile (AIBN), and the solvent can be anhydrous 1,4-dioxane.
[0109] The present invention does not specifically limit the method of deoxygenation treatment in step (2), as long as it can achieve the purpose of the present invention. For example, the freeze-thaw method can be used for deoxygenation treatment, that is, the above mixed solution is sequentially frozen with liquid nitrogen, vacuumed, and filled with nitrogen gas, and this cycle is repeated three times.
[0110] The present invention does not specifically limit the precipitation treatment method in step (2), as long as it can achieve the purpose of the present invention. For example, the precipitation treatment can be carried out by low temperature precipitation with poor solvent. That is, after the polymerization reaction is completed, the reaction system is rapidly cooled to room temperature of 20℃~25℃ (e.g., the temperature of the reaction system is cooled to room temperature within 30 minutes), and the reaction system is exposed to air to terminate the free radical reaction. Then, the reaction liquid in the reaction system is added to the poor solvent, and the solid in the reaction liquid precipitates. The solid precipitate is collected. The poor solvent can be diethyl ether, n-hexane or methanol at a temperature of 0℃~5℃.
[0111] The present invention does not specifically limit the purification method in step (2), as long as it can achieve the purpose of the present invention. For example, tetrahydrofuran (THF) or dichloromethane (DCM) can be used to redissolve the solid precipitate collected above, and the solution can be added to a poor solvent again to precipitate. This process is repeated 2 to 3 times to remove unreacted first monomer and / or second monomer, initiator and small molecule byproducts to obtain a pure polymer. If the polymer is difficult to precipitate due to the high content of polydioxane side chains, dialysis purification can be used. Specifically, tetrahydrofuran (THF) can be used to redissolve the solid precipitate collected above, and the solution can be poured into a dialysis bag with a suitable molecular weight cutoff (MWCO). A mixture of THF and methanol or a mixture of THF and water can be used as the external liquid. The dialysis bag can be immersed in the external liquid for dialysis. The external liquid can be changed multiple times during dialysis to obtain a pure polymer.
[0112] It is understood that the polymer of this invention is obtained by drying after purification. This invention does not specifically limit the drying method and conditions, as long as the purpose of this invention can be achieved. For example, vacuum drying can be used, with a drying temperature of 35℃~40℃ and a drying time of 24h~48h.
[0113] A third aspect of the present invention provides a composite electrolyte comprising a lithium salt and a polymer as described in the first aspect. This composite electrolyte possesses the technical effects corresponding to the aforementioned polymer, which will not be elaborated upon here.
[0114] In one specific embodiment, the lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(oxalato)borate, lithium difluorooxalato)borate, lithium perchlorate, and lithium bis(trifluoromethanesulfonyl)imide; the mass ratio of lithium salt to polymer is (10~40):(60~90). By using the above-mentioned lithium salt, the composite electrolyte possesses sufficient ion transport capability while maintaining good film-forming properties and electrochemical stability, thereby ensuring the structural integrity and interfacial contact stability of the electrode during charge and discharge, and improving the rate performance and cycle performance of the solid-state battery. Furthermore, by controlling the mass ratio of lithium salt to polymer within the above-mentioned range, it is beneficial to allow the lithium salt to dissociate within the polymer chain to form sufficient migratable lithium ions. These ions, in conjunction with the etheroxy groups in the polymer that have a coordinating effect, construct a continuous and interconnected ion transport pathway, effectively improving the ion conduction efficiency inside the negative electrode, reducing the internal transport impedance of the electrode, and thus improving the initial coulombic efficiency and rate performance of the solid-state battery.
[0115] For example, the mass ratio of lithium salt to polymer can be 10:90, 15:85, 20:80, 25:75, 30:70, 35:65 or 40:60, or a range of any two of these values.
[0116] When a lithium salt comprises multiple specific materials as described above, the present invention does not impose specific limitations on the proportions between the various specific materials.
[0117] This invention does not specifically limit the source of lithium salts; commercially available products or products prepared by conventional methods well known to those skilled in the art are acceptable.
[0118] In one embodiment, the composite electrolyte is prepared by a preparation method comprising the following steps:
[0119] The mixture system including the polymer, lithium salt and solvent of the present invention is heated at 60°C to 80°C to fully dissolve the polymer and lithium salt in the solvent to obtain a composite electrolyte.
[0120] For example, the temperature of the heat treatment can be 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, 72°C, 74°C, 76°C, 78°C or 80°C, or a range of any two of these values.
[0121] Specifically, during the heat treatment, the mixture including the polymer, lithium salt, and solvent can be stirred to ensure that the lithium salt and polymer are fully dissolved in the solvent.
[0122] The present invention does not specify the stirring method. Conventional methods in the art can be used for stirring, as long as the purpose of the present invention can be achieved. For example, magnetic stirring, mechanical stirring and other methods can be used for stirring.
[0123] The present invention does not impose a specific limit on the solid content of the composite electrolyte, which can be adjusted according to the actual situation, as long as the purpose of the present invention can be achieved. For example, the solid content of the composite electrolyte can be 5% to 10%.
[0124] The present invention does not impose a specific limit on the heat treatment time, which can be adjusted according to the actual situation, as long as the purpose of the present invention can be achieved. For example, the heat treatment time can be 12h to 48h.
[0125] The present invention does not specifically limit the type of solvent in the preparation process of the above-mentioned composite electrolyte, as long as it can achieve the purpose of the present invention. For example, the solvent may include at least one of isobutyl isobutyrate, diethyl succinate, ethyl acetate, butyl acetate, butyl butyrate, octyl acetate, and anisole.
[0126] When the solvent includes multiple specific solvents mentioned above, the present invention does not impose specific limitations on the proportions between the various specific solvents.
[0127] A third aspect of the present invention provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active layer comprises the composite electrolyte of the second aspect. This negative electrode sheet has the technical effects corresponding to the polymers described above, which will not be elaborated further here.
[0128] The present invention does not impose specific limitations on the thickness of the negative electrode current collector and the negative electrode active layer, which can be adjusted according to the actual situation, as long as the purpose of the present invention can be achieved.
[0129] In one specific embodiment, the total mass percentage of polymer and lithium salt in the negative electrode active layer is 2.0% to 8.0%, based on the mass of the negative electrode active layer. By controlling the total mass percentage of polymer and lithium salt in the negative electrode active layer to be within the above range, it is beneficial to improve the ion conductivity within the negative electrode and enhance the interfacial adhesion between the components within the negative electrode, while also helping to reduce the loss of energy density in solid-state batteries.
[0130] For example, the total mass percentage of the polymer and lithium salt can be 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5% or 8.0%, or a range of any two of these values.
[0131] In one specific embodiment, the negative electrode active layer further includes a solid electrolyte, which includes Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 Li 10 GeP2S 12At least one of the above-mentioned solid electrolytes. By selecting the above-mentioned solid electrolyte, it is beneficial to construct a continuous ion transport network inside the electrode, effectively reducing the ion transport impedance inside the electrode; at the same time, the above-mentioned sulfide solid electrolyte has excellent mechanical ductility, which can plastically adapt to the volume deformation of silicon-containing materials, alleviate interparticle stress, reduce the risk of bonding failure and ion transport channel breakage, and maintain the ion conduction network inside the electrode for a long time; in addition, it is beneficial to improve the interfacial contact between the negative electrode and the solid electrolyte sheet, reduce the solid-solid interface impedance, thereby further improving the rate performance and first coulombic efficiency of the solid battery.
[0132] When the solid electrolyte includes multiple specific materials as described above, the present invention does not impose specific limitations on the proportions between the various specific materials.
[0133] This invention does not specifically limit the source of the solid electrolyte; any commercially available product or product prepared by conventional methods well known to those skilled in the art is acceptable.
[0134] In one specific embodiment, the negative electrode active layer further includes a binder, which includes at least one selected from polyisobutylene, styrene-ethylene-butene-styrene block copolymer, hydrogenated nitrile butadiene rubber, nitrile butadiene rubber, and styrene-butadiene rubber. By selecting the above-mentioned binder, it is beneficial to synergistically improve the cohesive strength and interfacial adhesion performance of the negative electrode sheet, thereby improving the cycle stability of the solid-state battery while taking into account both the rate performance and the initial coulombic efficiency.
[0135] When the adhesive includes multiple specific materials as described above, the present invention does not impose specific limitations on the proportions between the various specific materials.
[0136] This invention does not specifically limit the source of the adhesive; any commercially available product or product prepared by conventional methods well known to those skilled in the art can be used.
[0137] This invention does not impose specific limitations on the molecular weight (including weight-average molecular weight and number-average molecular weight) of the adhesive. Those skilled in the art can choose according to the actual situation, as long as the purpose of this invention can be achieved.
[0138] The present invention does not specifically limit the type of negative electrode current collector, which can be a conventional choice in the art, as long as it can achieve the purpose of the present invention, such as at least one of copper foil, nickel foam, and copper foam.
[0139] It is understood that the negative electrode active layer of the present invention also includes a negative electrode active material and a conductive agent. The present invention does not specifically limit the types of negative electrode active materials and conductive agents, and they can be conventional choices in the art. For example, the negative electrode active material may include at least one of graphite, hard carbon, soft carbon, mesophase carbon microspheres, silicon-based negative electrode materials (mainly including silicon suboxide and silicon-carbon negative electrodes), tin-based negative electrode materials (mainly including tin and tin alloys), etc., and the conductive agent may include at least one of conductive carbon black, acetylene black, graphene, Ketjen black, and carbon fiber.
[0140] This invention does not specifically limit the preparation method of the negative electrode, as long as it can achieve the purpose of this invention. For example, the preparation method of the positive electrode may include, but is not limited to:
[0141] The negative electrode active material, solid electrolyte, conductive agent, binder and the above composite electrolyte are mixed to obtain a mixture. The mixture is dispersed in a solvent and stirred thoroughly to form a uniform negative electrode slurry. The negative electrode slurry is uniformly coated on the negative electrode current collector, and after drying, rolling and cutting, a negative electrode sheet is obtained.
[0142] This invention does not impose any particular limitation on the solvents used, as long as the objective of this invention can be achieved. For example, the solvent may include at least one of isobutyl isobutyrate, diethyl succinate, ethyl acetate, butyl acetate, butyl butyrate, octyl acetate, and anisole. This invention does not impose any particular limitation on the solid content of the negative electrode slurry, as long as the objective of this invention can be achieved. This invention does not impose any particular limitation on the drying time and temperature, as long as the objective of this invention can be achieved. This invention does not impose any particular limitation on the rolling process parameters, as long as the objective of this invention can be achieved.
[0143] A fourth aspect of the present invention provides a solid-state battery, including the negative electrode sheet of the third aspect. This solid-state battery has the technical effects corresponding to the polymer described above, which will not be elaborated further here.
[0144] In one specific embodiment, the solid-state battery is a semi-solid mold half-cell, which further includes a solid electrolyte sheet. Along the thickness direction of the solid electrolyte sheet, the solid electrolyte sheet includes a first surface and a second surface. The first surface is impregnated with an ionic liquid and is disposed facing the negative electrode. Through the above arrangement, the excellent interfacial wettability of the ionic liquid can be used to fill the microscopic gaps between the solid electrolyte sheet and the negative electrode, constructing a highly conductive liquid-phase ion transport transition layer. At the same time, the ionic liquid can adapt to the volume deformation of the negative electrode during charging and discharging, maintaining effective contact between the negative electrode and the solid electrolyte sheet, thereby significantly reducing the solid-solid interface impedance on the negative electrode side, improving lithium-ion transport kinetics, and enabling the solid-state battery to have higher rate performance.
[0145] It is understood that the solid electrolyte sheet in a semi-solid-state battery includes a solid electrolyte. This invention does not specifically limit the type of solid electrolyte, as long as it achieves the purpose of this invention. For example, solid electrolytes include Li6PS5Cl, Li... 5.5 PS 4.5 Cl 1.5 Li 10 GeP2S 12 At least one of them.
[0146] In one specific embodiment, the ionic liquid includes at least one of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bisfluorosulfonylimide, 1-n-butyl-1-methylpyrrolidineonium bisfluorosulfonylimide, 1-ethyl-3-methylimidazolium bistrifluoromethanesulfonylimide, 1-methyl-3-hexylimidazolium fluoromethanesulfonylimide, N-ethyl-N-methylpyrrolidine bis(fluorosulfonic acid)imide, N-propyl-N-methylpyrrolidine bis(fluorosulfonic acid)imide, and 1-methyl-1-propyl-3-fluoropyrrole bis(fluorosulfonic acid)imide. The aforementioned ionic liquid can preferentially undergo controlled reduction during the first charge cycle, forming a dense and stable LiF-rich SEI film on the negative electrode surface. This effectively suppresses irreversible side reactions at the negative electrode interface, reduces permanent loss of active lithium, and further improves the first coulombic efficiency of the solid-state battery.
[0147] When an ionic liquid includes multiple specific materials as described above, the present invention does not impose specific limitations on the proportions between the various specific materials.
[0148] This invention does not specifically limit the source of the ionic liquid; any commercially available product or product prepared by conventional methods well known to those skilled in the art is acceptable.
[0149] In one specific embodiment, the ionic liquid accounts for a mass percentage w of the solid electrolyte sheet, where 15% ≤ w ≤ 25%. By controlling the value of w within the above range, it is beneficial to ensure that the ionic liquid fully fills the microscopic gaps between the solid electrolyte sheet and the negative electrode sheet, constructs an efficient lithium-ion transport channel, and improves the rate performance of the solid-state battery. At the same time, it is beneficial to form a dense and stable SEI film on the negative electrode surface, reduce irreversible active lithium consumption, and significantly improve the first coulombic efficiency of the solid-state battery.
[0150] For example, the value of w can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, or 25%, or a range of any two of these values.
[0151] It should be noted that the solid-state battery in this invention can also be a solid-state full battery, which includes all-solid-state full batteries and semi-solid-state full batteries. Generally, a solid-state full battery includes a cell, a casing for encapsulating the cell, and other components known in the art. This invention does not limit the aforementioned other components. This invention does not specifically limit the material of the casing; conventional casing materials in the art, such as aluminum-plastic film, can be used to encapsulate the cell.
[0152] When the solid-state full cell is an all-solid-state full cell, the cell includes a positive electrode and a solid electrolyte layer located between the negative electrode and the positive electrode, in addition to the aforementioned negative electrode. When the solid-state full cell is a semi-solid-state full cell, the cell includes a positive electrode, a separator between the positive electrode and the negative electrode, and a gel electrolyte system, in addition to the aforementioned negative electrode. The gel electrolyte system includes an electrolyte and a polymer matrix.
[0153] The present invention does not specifically limit the structure of the positive electrode sheet. In one embodiment, the positive electrode sheet includes a positive current collector and a positive active layer disposed on the surface of the positive current collector.
[0154] The present invention does not specifically limit the type of positive current collector, which can be any conventional choice in the art, as long as it can achieve the purpose of the present invention, such as any one of aluminum foil or nickel foil.
[0155] The present invention does not impose specific limitations on the thickness of the positive electrode current collector and the positive electrode active layer, which can be selected according to the actual situation, as long as the purpose of the present invention can be achieved.
[0156] In this invention, the positive electrode active layer includes a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent. This invention does not specifically limit the types of positive electrode active material, positive electrode binder, and positive electrode conductive agent; they can be conventional choices in the art, as long as they achieve the purpose of this invention. For example, the positive electrode active material can be a composite oxide of lithium with at least one of the metals cobalt, manganese, nickel, or combinations thereof. More specifically, it can be at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium manganese oxide, nickel-cobalt-manganese ternary materials, nickel-cobalt-aluminum ternary materials, lithium iron phosphate (LFP), lithium nickel manganese oxide, lithium-rich manganese-based materials, etc.; the positive electrode binder can include at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, and polyurethane; the positive electrode conductive agent can include at least one of conductive carbon black, acetylene black, graphene, Ketjen black, and carbon fiber.
[0157] Furthermore, the positive electrode active layer also includes a solid electrolyte. This invention does not specifically limit the type of solid electrolyte in the positive electrode active layer; any commonly used choice in the art is acceptable, as long as it achieves the purpose of this invention. For example, the solid electrolyte in the positive electrode active layer can be selected from Li6PS5Cl, Li... 5.5 PS 4.5 Cl 1.5 Li 10 GeP2S 12 At least one of them.
[0158] This invention does not impose any particular limitation on the mass percentage of each component in the positive electrode active layer. Those skilled in the art can choose according to the actual situation, as long as the purpose of this invention can be achieved.
[0159] This invention does not specifically limit the composition of the solid electrolyte layer, as long as it achieves the purpose of this invention. For example, the solid electrolyte layer includes a solid electrolyte and an optional binder, wherein "optional" means that the solid electrolyte layer may or may not contain a binder.
[0160] This invention does not specifically limit the types of solid electrolyte in the solid electrolyte layer or the optional binder; any conventional choices in the art can be used, as long as they achieve the purpose of this invention. For example, the solid electrolyte in the solid electrolyte layer can be selected from Li6PS5Cl, Li 5.5 PS 4.5 Cl 1.5 Li 10 GeP2S 12 At least one of the following, the binder in the solid electrolyte layer may be selected from at least one of polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), and polyethylene oxide (PEO).
[0161] The present invention does not impose a specific limit on the thickness of the solid electrolyte layer, which can be selected according to the actual situation, as long as the purpose of the present invention can be achieved.
[0162] The polymer matrix in this invention refers to a three-dimensional network polymer skeleton structure formed by polymer monomers through polymerization and cross-linking reactions, which can encapsulate and bind the liquid electrolyte, causing the system to change from a liquid state to a gel semi-solid state.
[0163] This invention does not specifically limit the type of polymer monomer; any conventional choice in the art can be used, as long as it achieves the purpose of this invention.
[0164] This invention does not specifically limit the electrolyte, as long as it can achieve the purpose of this invention. For example, the electrolyte includes an electrolyte and an organic solvent. The organic solvent may include at least one of the following: ethylene carbonate, propylene carbonate, butene carbonate, fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), diethyl carbonate (DEC), difluoroethylene carbonate (DFEC), dipropyl carbonate, methyl ethyl carbonate (EMC), ethyl acetate, ethyl propionate, propyl acetate, propyl propionate, sulfolane, and γ-butyrolactone. The electrolyte may be at least one of the following: lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI).
[0165] This invention does not specifically limit the type of diaphragm, as long as it achieves the purpose of the invention. For example, the diaphragm material may include, but is not limited to, at least one of polyethylene (PE), polyolefins (PO) primarily composed of polypropylene (PP), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid. The type of diaphragm may include at least one of woven membrane, nonwoven membrane, microporous membrane, composite membrane, rolled membrane, or spun membrane. The diaphragm of this invention may have a porous structure, and this invention does not particularly limit the pore size of the porous structure of the diaphragm, as long as it achieves the purpose of the invention. This invention does not particularly limit the thickness of the diaphragm, as long as it achieves the purpose of the invention.
[0166] This invention does not impose any particular restrictions on the preparation methods of all-solid-state full cells and semi-solid-state full cells. Any preparation method known in the art can be used, as long as it can achieve the purpose of this invention.
[0167] The present invention will be further described below through specific embodiments. It should be noted that the performance verification below uses a solid-state mold half-cell. Those skilled in the art can adapt the polymer of the present invention to solid-state full cells based on the verification results, and the same technical effects can be achieved.
[0168] Unless otherwise specified, the reagents, materials and instruments used in the following examples are all conventional reagents, materials and instruments in the art, and can be obtained commercially. The reagents involved can also be synthesized by conventional methods in the art.
[0169] Example 1
[0170] (1) Preparation of the first monomer with the structural formula CH2=CH-(CH2CH2OCH2O)8-CH3:
[0171] 1,3-Dioxolane and 3-buten-1-ol were dried over a 4 Å molecular sieve for 24 h before use. All solvents used were anhydrous, and nitrogen protection was maintained throughout the preparation process. 3-Buten-1-ol and anhydrous toluene were added to a dried Schlenk flask to obtain a mixture, and the temperature of the mixture was lowered to 0°C using an ice bath. 1,3-Dioxolane was added to the mixture, and after thorough stirring, the cationic ring-opening polymerization catalyst boron trifluoride diethyl ether complex was added to obtain a mixed solution. The temperature of the mixture was maintained at 0°C during the addition process, and then kept at 0°C for 1.5 h. In the aforementioned mixed solution, the molar ratio of 3-buten-1-ol to 1,3-dioxolane was 1:8, the total concentration of 3-buten-1-ol and 1,3-dioxolane was 2.25 mol / L, and the concentration of 3-buten-1-ol was... The total molar ratio of 1,3-dioxolane to the molar ratio of boron trifluoride diethyl ether complex was 600. After the incubation period, the temperature was raised to 25°C for the reaction, which was completed after 8 hours. Triethylamine was then added to the reaction system in an ice bath (0°C) to quench the reaction. The reaction system was separated into liquid and liquid phases. The organic phase was collected and washed with water and brine. Anhydrous magnesium sulfate was added to the washed organic phase for drying. Magnesium sulfate was removed by filtration. The filtrate was subjected to low-temperature (35°C) rotary evaporation to remove solvent and unreacted small molecule impurities, yielding an intermediate with the structural formula CH2=CH-(CH2CH2OCH2O)8-H.
[0172] The above 0.012 mol intermediate was dissolved in 65 mL of anhydrous THF to obtain a mixed solution, and the temperature of the mixed solution was lowered to 0 °C by an ice bath. Under a nitrogen atmosphere, 0.012 mol of NaH was added to the mixed solution and reacted for 30 min to generate an alkoxide. After the reaction was completed, 0.012 mol of CH3I was added to the reaction system for methylation end-capping. After the addition was completed, the mixture was stirred at 0 °C for 30 min, and then the temperature was raised to 25 °C to continue the reaction. The reaction was stopped after 8 h. Then, methanol was added to the reaction system in an ice bath (0 °C) to quench the reaction, and water was added for dilution. The mixture was extracted with DCM to obtain the first monomer with the structural formula CH2=CH-(CH2CH2OCH2O)8-CH3.
[0173] (2) Preparation of polymer:
[0174] Add the first monomer CH2=CH-(CH2CH2OCH2O)8-CH3, the second monomer CH2=CH-C(=O)-O-CF3, the chain transfer agent DDMAT, the initiator AIBN, and the solvent anhydrous 1,4-dioxane to a dry Schlenk tube to obtain a mixed solution. In this mixed solution, the total molar concentration of the first and second monomers is 0.5 mol / L, the molar ratio of the first and second monomers is 2:80, the ratio of the total molar amount of monomers to the molar amount of chain transfer agent is 82.3, and the molar amount of initiator accounts for 0.18% of the total molar amount of monomers. The mixed solution is then subjected to liquid nitrogen freezing, vacuuming, and nitrogen purging in sequence three times, and the Schlenk tube is sealed.
[0175] The reaction tube was placed in a 65°C oil bath for polymerization, and the reaction was stopped after 12 hours. The system was then rapidly cooled to room temperature (25°C) within 30 minutes and exposed to air to terminate the free radical reaction. The reaction solution was then added to diethyl ether at 0°C, where the solid in the reaction solution precipitated. The solid precipitate was collected. The collected solid precipitate was redissolved with THF, and the solution was added back to diethyl ether to precipitate again. This process was repeated three times to obtain a pure polymer. The polymer was then dried at 38°C for 36 hours to obtain the polymer of this embodiment.
[0176] The polymer includes block A and block B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x=8, R is -CF3, the number of repeating units m of block A is 2, the number of repeating units n of block B is 80, the number average molecular weight of block A is 1268 g / mol, the number average molecular weight of block B is 11200 g / mol, and the number average molecular weight Mn of the polymer is 12468 g / mol.
[0177] (3) Preparation of composite electrolyte:
[0178] The lithium salt bis(trifluoromethanesulfonyl)imide lithium and the polymer prepared above were added to the solvent diethyl succinate at a mass ratio of 30:70 to obtain a mixed system. The mixed system was magnetically stirred and heated to 70°C and maintained at this temperature for 12 hours to obtain the composite electrolyte of this embodiment, which has a solid content of 5%.
[0179] (4) Preparation of negative electrode:
[0180] The composite electrolyte, the silicon-carbon composite material (containing 70% silicon and 30% carbon by mass), the solid electrolyte Li6PS5Cl, the conductive agent conductive carbon black, and the binder styrene-butadiene rubber were uniformly mixed to obtain a mixture. The mass ratio of the total mass of lithium salt and polymer, the mass of the negative electrode active material, the mass of the solid electrolyte, the mass of the conductive agent, and the mass of the binder in this mixture was 4:70:20.5:1.5:4. This mixture was dissolved in anisole and thoroughly stirred to form a uniform negative electrode slurry with a solid content of 45%. This negative electrode slurry was uniformly coated onto one surface of a copper foil (8 μm thick) as the negative electrode current collector, with a coating density of 4.5 mg / cm³. 2 After drying at 120℃, the material is rolled and slit to obtain a negative electrode sheet with a negative electrode active layer on its surface. The compacted density of the negative electrode active layer is 1.1 g / cm³. 3 Based on the mass of the negative electrode active layer, the total mass percentage of polymer and lithium salt is 4.0%.
[0181] (5) Preparation of solid electrolyte sheets:
[0182] Take 150 mg of solid electrolyte Li6PS5Cl powder and press it into a solid electrolyte sheet by holding it in a mold at a pressure of 375 MPa for 5 min.
[0183] (6) Preparation of all-solid-state mold half-cells:
[0184] The negative electrode sheet prepared above is placed on one side of the above-mentioned solid electrolyte sheet, and a lithium indium electrode sheet is placed on the other side to assemble the all-solid-state mold half-cell of this embodiment.
[0185] Example 2
[0186] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in Example 1, except that in step (2), a monomer with the structural formula CH2=CH-C(=O)-O-CH2CF3 is used as the second monomer.
[0187] The prepared polymer includes block A and block B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x=8, R is -CH2CF3, the number of repeating units m of block A is 2, the number of repeating units n of block B is 80, the number average molecular weight of block A is 1268 g / mol, the number average molecular weight of block B is 12320 g / mol, and the number average molecular weight Mn of the polymer is 13588 g / mol.
[0188] Example 3
[0189] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in Example 1, except that: in step (2), a monomer with the structural formula CH2=CH-C(=O)-OC(CF3)3 is used as the second monomer. The preparation method of the CH2=CH-C(=O)-OC(CF3)3 monomer is as follows:
[0190] A magnetic stir bar was added to a dry three-necked flask, and high-purity argon gas was introduced to purge the air from the flask three times, maintaining a slight positive pressure throughout. 120 mL of anhydrous dichloromethane, 23.60 g of tris(trifluoromethyl)methanol, 2.5 mg of polymerization inhibitor MEHQ, and 11.13 g of anhydrous triethylamine were added to the flask to obtain a mixed solution. The temperature of the mixed solution was lowered to -10°C, and stirring was started. 9.50 g of freshly distilled acryloyl chloride was transferred to a constant-pressure dropping funnel, with an argon balloon attached to the top of the funnel to prevent water from entering. A three-necked flask was connected to the lower end of a funnel. Freshly distilled acryloyl chloride was slowly and uniformly added dropwise to the mixed solution with stirring, keeping the temperature of the mixed solution ≤ -5℃ during the addition process. The addition time was 1.5 hours. After the addition was completed, the reaction was carried out at -10℃ for 12 hours. After the reaction was completed, the reaction system was kept at 0℃, and 50 mL of 0℃ saturated saline solution was added to quench the reaction system. The mixture was stirred continuously for 10 minutes. The quenched system was then transferred to a separatory funnel and allowed to stand to separate into layers. The lower organic phase (dichloromethane layer, containing the second monomer) and the upper aqueous phase are separated to obtain the organic phase. The separated organic phase is mixed with 30 mL of 0℃ saturated brine and washed to remove triethylamine and water-soluble impurities. The washing step is repeated twice to obtain the washed organic phase. Anhydrous sodium sulfate is added to the washed organic phase and dried for 4 hours. The solid desiccant is removed by filtration to obtain the filtrate. The filtrate is removed by rotary evaporation (water bath ≤30℃ to prevent monomer thermal polymerization) at room temperature (25℃) to obtain the crude monomer product. The crude monomer product is loaded into a vacuum distillation apparatus. A small amount of basic alumina is added to the distillation flask beforehand to adsorb acidic impurities and inhibit polymerization. The vacuum degree is set to 10 mmHg, and the temperature is slowly increased (heating rate is 2℃ / min). The main fraction is collected: the colorless and transparent fraction with a pot temperature of 72℃ / 10 mmHg to 75℃ / 10 mmHg is the second monomer CH2=CH-C(=O)-OC(CF3)3.
[0191] The prepared polymer includes block A and block B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x=8, R is -C(CF3)3, the number of repeating units m of block A is 2, the number of repeating units n of block B is 80, the number average molecular weight of block A is 1268 g / mol, the number average molecular weight of block B is 23200 g / mol, and the number average molecular weight Mn of the polymer is 24468 g / mol.
[0192] Example 4
[0193] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in embodiment 1, except that in step (2), a monomer with the structural formula CH2=CH-C(=O)-O-Ph is used as the second monomer.
[0194] The prepared polymer includes blocks A and blocks B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x=8, R is -Ph, the number of repeating units m of block A is 2, the number of repeating units n of block B is 80, the number average molecular weight of block A is 1268 g / mol, the number average molecular weight of block B is 11840 g / mol, and the number average molecular weight Mn of the polymer is 13108 g / mol.
[0195] Example 5
[0196] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in embodiment 1, except that: in step (2), the molar ratio of the first monomer and the second monomer is 1:20;
[0197] The prepared polymer includes block A and block B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x=8, R is -CF3, the number of repeating units m of block A is 1, the number of repeating units n of block B is 20, the number average molecular weight of block A is 634 g / mol, the number average molecular weight of block B is 2800 g / mol, and the number average molecular weight Mn of the polymer is 3434 g / mol.
[0198] Example 6
[0199] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in embodiment 1, except that: in step (2), the molar ratio of the first monomer and the second monomer is 5:160.
[0200] The prepared polymer includes block A and block B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x=8, R is -CF3, the number of repeating units m of block A is 5, the number of repeating units n of block B is 160, the number average molecular weight of block A is 3170 g / mol, the number average molecular weight of block B is 22400 g / mol, and the number average molecular weight Mn of the polymer is 25570 g / mol.
[0201] Example 7
[0202] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in Example 1, except that: in step (1), the molar ratio of 3-buten-1-ol and 1,3-dioxolane is 1:4, and the first monomer with the structural formula CH2=CH-(CH2CH2OCH2O)4-CH3 is prepared.
[0203] The prepared polymer includes blocks A and blocks B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x=4, R is -CF3, the number of repeating units m of block A is 2, the number of repeating units n of block B is 80, the number average molecular weight of block A is 676 g / mol, the number average molecular weight of block B is 11200 g / mol, and the number average molecular weight Mn of the polymer is 11876 g / mol.
[0204] Example 8
[0205] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in Example 1, except that: in step (1), the molar ratio of 3-buten-1-ol and 1,3-dioxolane is 1:15, and the resulting structure is CH2=CH-(CH2CH2OCH2O). 15 The first monomer of -CH3;
[0206] The prepared polymer includes blocks A and blocks B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x = 15, R is -CF3, the number of repeating units m of block A is 2, the number of repeating units n of block B is 80, the number-average molecular weight of block A is 2304 g / mol, the number-average molecular weight of block B is 11200 g / mol, and the number-average molecular weight Mn of the polymer is 13504 g / mol.
[0207] Example 9
[0208] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in Example 3, except that: in step (1), the molar ratio of 3-buten-1-ol and 1,3-dioxolane is 1:15, and the resulting structure is CH2=CH-(CH2CH2OCH2O). 15 The first monomer of -CH3;
[0209] In step (2), the molar ratio of the first monomer to the second monomer is 5:150;
[0210] The prepared polymer includes block A and block B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x=15, R is -C(CF3)3, the number of repeating units m of block A is 5, the number of repeating units n of block B is 150, the number average molecular weight of block A is 5760 g / mol, the number average molecular weight of block B is 43500 g / mol, and the number average molecular weight Mn of the polymer is 49260 g / mol.
[0211] Example 10
[0212] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in Example 1, except that in step (3), the mass ratio of lithium salt and polymer is 10:90.
[0213] Example 11
[0214] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in Example 1, except that in step (3), the mass ratio of lithium salt and polymer is 40:60.
[0215] Example 12
[0216] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in Example 1, except that in step (3), the mass ratio of lithium salt and polymer is 5:95.
[0217] Example 13
[0218] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in Example 1, except that in step (3), the mass ratio of lithium salt and polymer is 45:55.
[0219] Example 14
[0220] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in embodiment 4, except that: in step (4), the ratio of the total mass of lithium salt and polymer, the mass of negative electrode active material, the mass of solid electrolyte, the mass of conductive agent and the mass of binder in the mixture is 2:70:22.5:1.5:4; then based on the mass of the negative electrode active layer, the total mass percentage of polymer and lithium salt is 2%.
[0221] Example 15
[0222] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in embodiment 4. The difference is that in step (4), the ratio of the total mass of lithium salt and polymer, the mass of negative electrode active material, the mass of solid electrolyte, the mass of conductive agent and the mass of binder in the mixture is 8:70:16.5:1.5:4; then based on the mass of the negative electrode active layer, the total mass percentage of polymer and lithium salt is 8%.
[0223] Example 16
[0224] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in embodiment 4. The difference is that in step (4), the ratio of the total mass of lithium salt and polymer, the mass of negative electrode active material, the mass of solid electrolyte, the mass of conductive agent and the mass of binder in the mixture is 1:70:23.5:1.5:4; then based on the mass of the negative electrode active layer, the total mass percentage of polymer and lithium salt is 1%.
[0225] Example 17
[0226] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in embodiment 4, except that: in step (4), the ratio of the total mass of lithium salt and polymer, the mass of negative electrode active material, the mass of solid electrolyte, the mass of conductive agent and the mass of binder in the mixture is 10:70:14.5:1.5:4; then based on the mass of the negative electrode active layer, the total mass percentage of polymer and lithium salt is 10%.
[0227] Example 18
[0228] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in embodiment 4, except that: in step (3), the lithium salt is lithium bis(fluorosulfonyl)imide.
[0229] In step (4), the solid electrolyte is Li6PS. 4.5 Cl 1.5 The binder is polyisobutylene (weight average molecular weight of 1,000,000).
[0230] Example 19
[0231] The preparation method of the all-solid-state mold half-cell in this embodiment is basically the same as that in embodiment 4, except that: in step (3), the lithium salt is lithium difluorooxalate borate;
[0232] In step (4), the solid electrolyte is Li 10 GeP2S 12 The binder is a styrene-ethylene-butene-styrene block copolymer (weight average molecular weight of 400,000).
[0233] Example 20
[0234] This embodiment is basically the same as embodiment 1, except that: in step (5), ionic liquid 1-ethyl-3-methylimidazolium difluorosulfonylimide salt is dropped onto one side surface of the solid electrolyte sheet, and the ionic liquid accounts for 15% of the mass percentage of the solid electrolyte sheet;
[0235] In step (6), the negative electrode is placed on one side of the solid electrolyte sheet on which ionic liquid is added, and the lithium indium electrode is placed on the other side to assemble the semi-solid mold half-cell of this embodiment.
[0236] Example 21
[0237] The preparation method of the semi-solid mold half-cell in this embodiment is basically the same as that in embodiment 20, except that: in step (5), the ionic liquid accounts for 20% of the mass of the solid electrolyte sheet.
[0238] Example 22
[0239] The preparation method of the semi-solid mold half-cell in this embodiment is basically the same as that in embodiment 20, except that: in step (5), the ionic liquid accounts for 25% of the mass percentage of the solid electrolyte sheet.
[0240] Example 23
[0241] The preparation method of the semi-solid mold half-cell in this embodiment is basically the same as that in embodiment 20, except that: in step (5), the ionic liquid accounts for 6% of the mass of the solid electrolyte sheet.
[0242] Example 24
[0243] The preparation method of the semi-solid mold half-cell in this embodiment is basically the same as that in Example 20, except that: in step (5), the ionic liquid is 1-n-butyl-1-methylpyrrolidone difluorosulfonylimide salt.
[0244] Example 25
[0245] The preparation method of the semi-solid mold half-cell in this embodiment is basically the same as that in Example 20, except that: in step (5), the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide salt.
[0246] Example 26
[0247] The preparation method of the semi-solid mold half-cell in this embodiment is basically the same as that in Example 20, except that: in step (5), the ionic liquid is N-propyl-N-methylpyrrolidine bis(fluorosulfonic acid)imine.
[0248] Comparative Example 1
[0249] The preparation method of the all-solid-state mold half-cell in this comparative example is basically the same as that in Example 1. The difference is that in step (4), the mixture does not contain composite electrolyte, that is, the mass ratio of the negative electrode active material, the solid electrolyte, the conductive agent and the binder in the mixture is 70:24.5:1.5:4.
[0250] Comparative Example 2
[0251] The preparation method of the all-solid-state mold half-cell in this comparative example is basically the same as that in Example 1, except that in step (2), a monomer with the structural formula CH2=CH-C(=O)-O-CH3 is used as the second monomer.
[0252] The prepared polymer includes block A and block B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x=8, R is -CH3, the number of repeating units m of block A is 2, the number of repeating units n of block B is 80, the number average molecular weight of block A is 1268 g / mol, the number average molecular weight of block B is 6880 g / mol, and the number average molecular weight Mn of the polymer is 8148 g / mol.
[0253] Comparative Example 3
[0254] The preparation method of the all-solid-state mold half-cell in this comparative example is basically the same as that in Example 1, except that in step (1), the molar ratio of 3-buten-1-ol and 1,3-dioxolane is 1:2, and the first monomer with the structural formula CH2=CH-(CH2CH2OCH2O)2-CH3 is prepared.
[0255] In step (2), there is no second monomer in the mixed solution; the polymer obtained does not contain block B, and block A is the structural unit shown in Formula 1, where x=2, the number of repeating units m of block A is 2, the number average molecular weight of block A is 380 g / mol, and the number average molecular weight Mn of the polymer is 380 g / mol.
[0256] Comparative Example 4
[0257] The preparation method of the all-solid-state mold half-cell in this comparative example is basically the same as that in Example 1, except that: in step (2), there is no second monomer in the mixed solution; the polymer obtained does not contain block B, and block A is the structural unit shown in Formula 1, where x=8, the number of repeating units m of block A is 2, the number average molecular weight of block A is 1268g / mol, and the number average molecular weight Mn of the polymer is 1268g / mol.
[0258] Comparative Example 5
[0259] The preparation method of the all-solid-state mold half-cell in this comparative example is basically the same as that in Example 1, except that in step (1), the molar ratio of 3-buten-1-ol and 1,3-dioxolane is 1:12, and the resulting structure is CH2=CH-(CH2CH2OCH2O). 12 The first monomer of -CH3;
[0260] In step (2), there is no second monomer in the mixed solution;
[0261] The prepared polymer contains no block B, and block A is the structural unit shown in Formula 1, where x=12, the number of repeating units m of block A is 2, the number-average molecular weight of block A is 1860 g / mol, and the number-average molecular weight Mn of the polymer is 1860 g / mol.
[0262] Comparative Example 6
[0263] The preparation method of the all-solid-state mold half-cell in this comparative example is basically the same as that in Example 1, except that in step (1), the molar ratio of 3-buten-1-ol and 1,3-dioxolane is 1:2, and the first monomer with the structural formula CH2=CH-(CH2CH2OCH2O)2-CH3 is prepared.
[0264] The prepared polymer includes blocks A and blocks B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x=2, R is -CF3, the number of repeating units m of block A is 2, the number of repeating units n of block B is 80, the number-average molecular weight of block A is 380 g / mol, the number-average molecular weight of block B is 11200 g / mol, and the number-average molecular weight Mn of the polymer is 11580 g / mol.
[0265] Comparative Example 7
[0266] The preparation method of the all-solid-state mold half-cell in this comparative example is basically the same as that in Example 1, except that in step (1), the molar ratio of 3-buten-1-ol and 1,3-dioxolane is 1:17, and the first monomer with the structural formula CH2=CH-(CH2CH2OCH2O)2-CH3 is prepared.
[0267] The prepared polymer includes blocks A and blocks B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x = 17, R is -CF3, the number of repeating units m of block A is 2, the number of repeating units n of block B is 80, the number-average molecular weight of block A is 2600 g / mol, the number-average molecular weight of block B is 11200 g / mol, and the number-average molecular weight Mn of the polymer is 13800 g / mol.
[0268] Comparative Example 8
[0269] The preparation method of the all-solid-state mold half-cell in this comparative example is basically the same as that in Example 1, except that: in step (2), there is no first monomer in the mixed solution;
[0270] The prepared polymer contains no block A, and block B is the structural unit shown in Formula 2, wherein the number of repeating units n of block B is 80, the number average molecular weight of block B is 11200 g / mol, and the number average molecular weight Mn of the polymer is 11200 g / mol.
[0271] Comparative Example 9
[0272] The preparation method of the semi-solid mold half-cell in this comparative example is basically the same as that in Example 1, except that in step (2), the molar ratio of the first monomer and the second monomer is 7:80.
[0273] The prepared polymer includes block A and block B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x=8, R is -CF3, the number of repeating units m of block A is 7, the number of repeating units n of block B is 80, the number average molecular weight of block A is 4438 g / mol, the number average molecular weight of block B is 11200 g / mol, and the number average molecular weight Mn of the polymer is 15638 g / mol.
[0274] Comparative Example 10
[0275] The preparation method of the all-solid-state mold half-cell in this comparative example is basically the same as that in Example 1, except that in step (2), the molar ratio of the first monomer and the second monomer is 2:15.
[0276] The polymer includes block A and block B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x=8, R is -CF3, the number of repeating units m of block A is 2, the number of repeating units n of block B is 15, the number average molecular weight of block A is 1268 g / mol, the number average molecular weight of block B is 2100 g / mol, and the number average molecular weight Mn of the polymer is 3368 g / mol.
[0277] Comparative Example 11
[0278] The preparation method of the semi-solid mold half-cell in this comparative example is basically the same as that in Example 1, except that in step (2), the molar ratio of the first monomer and the second monomer is 2:170.
[0279] The polymer includes block A and block B. Block A is the structural unit shown in Formula 1, and block B is the structural unit shown in Formula 2, where x = 8, R is -CF3, the number of repeating units m of block A is 2, the number of repeating units n of block B is 170, the number average molecular weight of block A is 1268 g / mol, the number average molecular weight of block B is 23800 g / mol, and the number average molecular weight Mn of the polymer is 25068 g / mol.
[0280] Test case
[0281] 1. The compatibility of the polymers prepared in the above examples and comparative examples in weakly polar solvents was tested using the following methods:
[0282] The polymer to be tested was added to a solvent (ethyl acetate or anisole) to obtain a mixed system with a solid content of 5%. The mixed system was magnetically stirred and heated to 70°C and kept at this temperature for 12 hours. The presence of no obvious suspended matter and the clarity of the mixed system were observed to determine whether the polymer was completely dissolved.
[0283] The test results are shown in Table 1.
[0284] 2. The peel strength of the negative electrode sheets prepared in the above embodiments and comparative examples was tested. The test method is as follows:
[0285] Cut the negative electrode sheet to be tested into small pieces of 25mm × 100mm to obtain the test sample. Use a lint-free cloth dampened with solvent such as alcohol to gently wipe the surface of the test sample without the negative electrode active layer to remove surface oil and impurities. Use double-sided tape to flatly attach the test sample with the negative electrode active layer facing down onto the stainless steel test plate, and roll it back and forth several times with a rubber roller to ensure that the electrode sheet and the double-sided tape are tightly adhered and to remove air bubbles. Manually pre-peel the negative electrode active layer of the test sample from the negative electrode current collector by 15mm to facilitate... Clamping; fix the test plate in the lower clamp of the tensile testing machine, clamp the pre-peeled negative electrode current collector end in the upper clamp, set the peeling speed to a constant rate of 300 mm / min, set the mode to 180° peeling, start the equipment, the upper clamp is stretched upward at a uniform speed, peeling the negative electrode current collector from the negative electrode active layer, the equipment will automatically record the force curve during the peeling process; take the average value of the stable segment in the peeling force curve (removing the initial peak and the end segment), and express it as peeling strength, that is, peeling force / sample width, in N / m.
[0286] The test results are shown in Table 1.
[0287] 3. The electrochemical performance of the all-solid-state mold half-cells and semi-solid-state mold half-cells prepared in the above examples and comparative examples was tested using the following methods:
[0288] (1) First Coulomb efficiency test:
[0289] The battery prepared above was tested at an ambient temperature of 30℃ using a battery testing instrument (Neware BTS4000). The operating pressure was set to 62.5MPa, the voltage window was 0.005V~1.5V, and the test rate was 0.1C. The initial discharge capacity C1 mAh / g and the initial charge capacity C2 mAh / g were obtained. The initial coulombic efficiency (%) was calculated as (C2 / C1)×100%.
[0290] (2) Ratio performance test:
[0291] The battery prepared above was tested using a battery testing instrument (Neware BTS4000) at an ambient temperature of 30℃. The operating pressure was set to 62.5MPa and the voltage window was 0.005V~1.5V. First, the battery was discharged at 0.1C and then charged at 0.1C. The 0.1C charging capacity was recorded as C3 mAh / g. Then, the battery was discharged at 0.1C and charged at 1C. The 1C charging capacity was recorded as C4 mAh / g. The 1C rate charging capacity retention rate (%) is calculated as (C4 / C3)×100%.
[0292] The test results are shown in Table 1.
[0293] Table 1
[0294]
[0295] In Table 1, " / " indicates that the data does not exist.
[0296] As shown in Table 1:
[0297] Compared to Comparative Examples 1 to 11, the solid-state molded half-cells and semi-solid-state molded half-cells in Examples 1 to 26 exhibit higher electrode peel strength, initial coulombic efficiency, and 1C rate capacity retention. Specifically, the electrode peel strength in Example 1 is 7.03 N / m, the initial coulombic efficiency of the all-solid-state molded half-cell is 91.63%, and the 1C rate capacity retention is 78.92%. In Example 20, the electrode peel strength is 7.03 N / m, the initial coulombic efficiency of the semi-solid-state molded half-cell is 93.12%, and the 1C rate capacity retention is 82.93%. The overall performance is significantly higher than that of the solid-state molded half-cells in the comparative examples, demonstrating higher initial coulombic efficiency and rate performance. Therefore, the polymer in this invention can simultaneously achieve ion transport efficiency, interface stability, and electrode structure integrity, thereby improving the initial coulombic efficiency and rate performance of solid-state batteries.
[0298] The above embodiments are merely preferred embodiments provided to fully illustrate the present invention, and the scope of protection of the present invention is not limited thereto. Equivalent substitutions or modifications made by those skilled in the art based on the present invention are all within the scope of protection of the present invention.
Claims
1. A polymer, characterized in that, The polymer comprises block A and block B, wherein block A is a structural unit shown in Formula 1 and block B is a structural unit shown in Formula 2. Formula 1, Formula 2; In Equation 1, x is an integer from 4 to 15; in Equation 2, R is selected from any one of the bases -CF3, -CH2CF3, -C(CF3)3, and -Ph. The number of repeating units in block A is m, 1≤m≤5, and the number of repeating units in block B is n, 20≤n≤160, where m and n are integers.
2. The polymer according to claim 1, characterized in that, The number-average molecular weight of the polymer is Mn, with a molecular weight of 3000 g / mol ≤ Mn ≤ 50000 g / mol.
3. A composite electrolyte, characterized in that, Includes lithium salts and the polymers described in claim 1 or 2.
4. The composite electrolyte according to claim 3, characterized in that, The lithium salt includes at least one of lithium bis(fluorosulfonyl)imide, lithium bis(oxalateborate)borate, lithium difluorooxalateborate, lithium perchlorate, and lithium bis(trifluoromethanesulfonyl)imide; the mass ratio of the lithium salt to the polymer is (10~40):(60~90).
5. A negative electrode sheet, characterized in that, The negative electrode sheet includes a negative electrode current collector and a negative electrode active layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active layer includes the composite electrolyte as described in claim 3 or 4.
6. The negative electrode sheet according to claim 5, characterized in that, Based on the mass of the negative electrode active layer, the total mass percentage of the polymer and the lithium salt is 2.0% to 8.0%.
7. The negative electrode sheet according to claim 5 or 6, characterized in that, The negative electrode active layer also includes a solid electrolyte, which includes Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 Li 10 GeP2S 12 At least one of them; And / or, the negative electrode active layer further includes a binder, the binder including at least one of polyisobutylene, styrene-ethylene-butene-styrene block copolymer, hydrogenated nitrile rubber, nitrile rubber, and styrene-butadiene rubber.
8. A solid-state battery, characterized in that, Includes the negative electrode sheet as described in any one of claims 5-7.
9. The solid-state battery according to claim 8, characterized in that, The solid-state battery is a semi-solid mold half-cell, which further includes a solid electrolyte sheet. Along the thickness direction of the solid electrolyte sheet, the solid electrolyte sheet includes a first surface and a second surface. The first surface is wetted with an ionic liquid and is disposed facing the negative electrode sheet.
10. The solid-state battery according to claim 9, characterized in that, The ionic liquid comprises at least one of the following: 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bisfluorosulfonylimide, 1-n-butyl-1-methylpyrrolidineonium bisfluorosulfonylimide, 1-ethyl-3-methylimidazolium bistrifluoromethylsulfonylimide, 1-methyl-3-hexylimidazolium fluoromethylsulfonylimide, N-ethyl-N-methylpyrrolidine bis(fluorosulfonic acid)imide, N-propyl-N-methylpyrrolidine bis(fluorosulfonic acid)imide, and 1-methyl-1-propyl-3-fluoropyrrole bis(fluorosulfonic acid)imide.
11. The solid-state battery according to claim 9 or 10, characterized in that, The ionic liquid accounts for a mass percentage (w) of the solid electrolyte sheet, where 15% ≤ w ≤ 25%.